Magnitude of postpartum morbidity and associated factors in southeast Ethiopia, 2022: A facility-based cross-sectional study - Feisal Hussein Hasen; Solomon Seyife Alemu; Derese Eshetu; Bedria Mohammed; Eden Nebi; Hana Israel; Yomilan Geneti; Lema Fikadu Wedajo; Woiynshet Gebretsadik (SAGE Open Medicine)
Objective: Maternal mortality in Ethiopia is estimated to be 205 per 100,000 live births, with postpartum morbidities expected to surpass maternal mortality substantially. Beside this, there is a lack of information on postpartum morbidities in the study area. Thus, the purpose of this study was to assess the magnitude of postpartum morbidities and associated factors in Bale Robe Town, southeast Ethiopia. Method: An institution-based cross-sectional study was employed among 371 from 1 April to 30 May 2022 among postpartum women attending postnatal care service in the Bale-Robe Town public health facilities. A face-to-face interviewer administered a structured questionnaire, and the participants were selected through a systematic random sampling technique. A bivariate analysis was performed to see the association between each independent variable and dependent variable, and variables with p -values less than 0.25 in the bivariate analysis were retrieved for multivariable analyses. A p -value of less than 0.05 indicated a 95% confidence interval as the level of statistical significance. Result: A total of 366 participants were involved in the study, giving us a response rate of 98.6%. The magnitude of postpartum morbidities among mothers was found to be 102 (27.9%), with a confidence interval of 95% CI: 23.3, 32.8. Women who hadn’t had antenatal care follow-up (AOR = 2.47, 95% CI: 1.36, 4.50), instrumental delivery (AOR = 2.69, 95% CI: 1.16, 6.26), unskilled birth attendant (AOR = 3.35, 95% CI: 1.06, 10.63), rural residence (AOR = 2.21, 95% CI: 1.26, 3.89), and current pregnancy-related morbidity or abnormality (AOR = 3.81, 95% CI: 2.00, 7.25) were significantly associated factors. Conclusion: This study revealed that the occurrence of postpartum morbidity in Bale Robe is a great health concern. Therefore, we recommend health professionals and health extension workers strengthen early detection and management of intrapartum abnormalities, give attention during instrumental deliveries, and strengthen skilled birth attendants.